Digital Literacy and Radicalism Potential: An Analysis of Youth Digital Behavior in South Sumatra: Literasi Digital dan Potensi Radikalisme: Analisis Perilaku Digital Generasi Muda di Sumatera Selatan - Dwiki Adi Putra; Isabella (Universitas Indo Global Mandiri, 2026)
Research Objective : This study aims to analyze the relationship between digital literacy, online behavior, and the Radicalism Potential Index (RPI), as well as to identify the level of vulnerability to radicalism among digital generations in South Sumatra. Design / Methodology : This research employs a quantitative approach using a survey method involving 400 respondents across generations (Gen Z, Millennials, Gen X, and Boomers). The variables measured include digital literacy, online behavior, RPI (ideology, attitudes, and actions), as well as internet usage patterns and digital platform preferences. Findings : The RPI increased from 9.3 in 2023 to 9.6 in 2024, with the attitude dimension being the most dominant (18.0), while the action dimension remained low (0.8). Most respondents spend more than three hours per day on the internet, with WhatsApp, Facebook, TikTok, and Instagram as the primary platforms. Low digital literacy is correlated with higher vulnerability to radical content. Practical Implications : There is a need to integrate Pancasila-based digital literacy into educational curricula, strengthen counter-narrative campaigns on digital platforms, and enhance multi-stakeholder collaboration to build a more resilient digital ecosystem. Originality / Value : This study integrates digital literacy, online behavior, and the Radicalism Potential Index within a single analytical framework and provides recent empirical data with a regional and cross-generational focus. Research Type : Research Paper.